Preparation method of flat lossless section sample of electrostatic spinning membrane

By using low boiling point solution and clip technology to brittle the electrospinning film in liquid nitrogen, the problems of easy destruction and high cost in the cross-section samples in the prior art are solved, and a flat and non-destructive cross-section samples are achieved, which is suitable for a wide range of applications.

CN119574602APending Publication Date: 2025-03-07HUBEI UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411710631.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to prepare a non-destructive cross-section sample of electrospun film, resulting in the original fiber morphology being destroyed, the pore structure changes, and the preparation cost is high.

Method used

The electrospinning film was completely infiltrated with a low boiling point solution, covered with clips and frozen, and then brittled in liquid nitrogen. After the solution was completely volatile, a flat and non-destructive cross-sectional sample was obtained.

Benefits of technology

The flat and non-destructive preparation of electrospinned film cross-section samples is realized, the original structure and pore distribution of the fiber are retained, the preparation cost is reduced, and it is suitable for a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119574602A_ABST
    Figure CN119574602A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an electrostatic spinning fiber membrane section sample. The preparation method comprises the following steps: firstly, fully infiltrating an electrostatic spinning membrane by utilizing a low-boiling-point solution; wrapping the soaked film with a clamping piece; the film is clamped and put into liquid nitrogen to be fully cooled; after full freezing, brittle fracture is carried out on the electrostatic spinning film in the middle part; and finally, taking out the middle electrostatic spinning film, and obtaining a flat and lossless electrostatic spinning film section sample after the solution is completely volatilized. The electrostatic spinning membrane obtained through the method is flat in section, the fiber structure and distribution are kept unchanged, and impurities except for the material of the electrostatic spinning membrane cannot be brought in.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sample preparation, and in particular to a method for preparing a sample of an electrostatic spinning membrane with a flat and lossless cross section. Background Art

[0002] Nanofiber is a new type of nanomaterial with extremely fine fiber diameter and high specific surface area. It has many excellent properties, which makes it widely used in many fields such as textiles, energy, biomedicine, etc.

[0003] In summary, the preparation and characterization of nanofiber materials is a hot topic in current research. Electrospinning has the advantages of simple manufacturing equipment, low spinning cost, a wide variety of spinnable materials, and controllable process. It has prepared a wide variety of nanofibers, including organic, organic / inorganic composite and inorganic electrospinning fibers.

[0004] In order to better analyze the properties of nanofiber materials, it is necessary to understand the detailed information such as the morphological characteristics, distribution and elemental composition of nanofibers. Since the movement of polymers is to rotate around single bonds, it is easy to move, so electrospun nanofibers have a high elongation, which can easily cause the original morphology of the fibers to be destroyed when subjected to force. At the same time, the interlaced distribution between many nanofibers has a huge porosity and does not have chemical bonding, so the nanofibers are easily disturbed, resulting in changes in fiber distribution. It is difficult to obtain non-destructive nanofiber samples for characterization with existing technologies, and it is urgent to further improve the sample preparation method to ensure the accuracy of material characterization.

[0005] In research, it is often necessary to use a scanning electron microscope to observe the original morphology of the cross section of electrospun membranes and electrospun fibers. The acquisition of traditional film cross sections usually includes the following methods: mechanical cutting, ion beam cutting, and frozen brittle fracture. However, these cross-section preparation methods have the following problems when applied to electrospun membranes: First, polymer nanofibers are very flexible, and direct mechanical cutting will produce obvious deformation, causing the cross section to be separated from the prototype, which is not conducive to observing the internal structure of the fiber, and is also prone to fiber disturbance, which greatly affects the direct observation of pore distribution; second, although ion beam cutting or laser cutting can avoid the problem of nanofiber extension and deformation during sample preparation to obtain a flat original cross section, its cost is too high and it does not have the conditions for widespread dissemination and use. Third, the commonly used freezing liquid is usually liquid nitrogen, and due to the limitations of the properties of the polymer material itself, electrospun nanofibers will still undergo toughness failure at this freezing temperature, and the fibers will undergo elongation and deformation. The fibers cannot be uniformly brittle fractured, which will change the cross-sectional morphology characteristics.

[0006] Patent application CN113686632A discloses a method for preparing cross-sections by using ultrapure water as an embedding agent and a filter membrane for cryosectioning, comprising the following steps: obtaining a water-soaked filter membrane, placing the filter membrane in a closed space, adding water to cover the filter membrane, and then cooling the filter membrane to freeze and solidify the filter membrane and water together, using a cryosectioning machine to cut the filter membrane, and obtaining a filter membrane cross-section sample after drying. This method is used to prepare filter membrane cross-sections. The filter membrane is usually a hydrophilic membrane with large membrane pores and is structurally different from an electrospinning membrane. This method is suitable for hydrophilic membranes with large pores and coarse fiber structures, and also requires the use of a cryosectioning machine, which is not suitable for the preparation of electrospinning membrane cross-sections.

[0007] Patent application CN105699167A discloses a processing method for preparing cross-sections by brittle fracture using a silicon wafer as a clip and a flexible film, comprising the following steps: processing the silicon wafer into a small, elongated strip to obtain a pre-grooved silicon wafer; bonding the pre-grooved silicon wafer to a flexible film; fixing the two ends with a clamp, and then placing them in a coolant to fully cool them; quickly taking out the frozen silicon wafer, and bending them toward the grooved surface of the frozen silicon wafer until the frozen silicon wafer breaks brittlely, thereby obtaining a brittle flexible film. This method uses a silicon wafer to limit the movement of the film and provides concentrated transient stress, thereby obtaining a complete cross-section sample at a low temperature. This method relies on the low-temperature environment provided by liquid nitrogen freezing to reduce the elongation of the polymer chain. In order to ensure the integrity of the cross section, it is necessary to ensure that the film composition is consistent. It has a better effect on single-component scraping films with complex entanglement of polymer chains, but is not applicable to electrospun nano-scale polymer fibers, nor to composite multi-component Janus films.

[0008] Patent application CN111721792A discloses a method for preparing polymer film cross-section samples using ion polishing technology, comprising the following steps: cutting the film material to be tested, placing the obtained film sample between two thin sheet-shaped clamps for stacking, forming a film sample assembly, and subjecting the film sample assembly to argon ion polishing to obtain the required film material cross-section scanning electron microscope sample. This method minimizes mechanical deformation, retains the original morphology of the membrane pore structure, and does not use other chemicals, thus avoiding contamination of the membrane material surface and ensuring the accuracy of sample detection. This method takes a long time to prepare microporous membrane cross-sections, has a small range, and is costly. It is suitable for the preparation of a small amount of samples and is not widely applicable. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the problems of uneven fracture, changed pore structure and destroyed fiber surface structure in the production of existing electrospinning membrane cross-section samples, and to provide a method which is simple to operate, low in cost and suitable for preparing lossless cross-sections of electrospinning membranes.

[0010] In order to solve the above technical problems, the present invention provides a technical solution: a method for preparing a flat and lossless cross-section sample of an electrospinning membrane, comprising the following steps:

[0011] S1: Use low boiling point solution to completely wet the electrospun membrane and remove residual bubbles;

[0012] S2: Use a clamp to completely cover and clamp the electrospun membrane to form a membrane sheet, and place the membrane sheet in liquid nitrogen to fully cool it;

[0013] S3: brittle fracture of electrospun membrane after cooling;

[0014] S4: Take out the middle electrospun membrane and wait for the solution to evaporate completely to obtain a smooth and intact electrospun brittle membrane sample.

[0015] Preferably, the low boiling point solution comprises a homogeneous solution prepared from any one of methanol, ethanol, isopropanol, and dichloromethane, or a combination of two or more thereof.

[0016] Preferably, the soaking time in S1 is greater than 30 minutes, and the removal of residual bubbles includes sending the soaked electrospun membrane into a vacuum machine for vacuuming for 1 minute.

[0017] Preferably, S1 comprises immersing the electrospinning membrane in a low boiling point solution under a low vacuum environment.

[0018] Preferably, the clip has a flat surface and is tough under liquid nitrogen freezing, and comprises a sheet made of PET, TPU, or PVC material.

[0019] Preferably, S2 further comprises immersing the clamped membrane twice in a low boiling point solution and then cooling it with liquid nitrogen, and the immersion time is greater than 30 seconds.

[0020] Preferably, in S2, liquid nitrogen is used to fully freeze the composite clip, and the freezing time is greater than 1 minute until the solution in the electrospinning membrane is completely solidified. Tweezers are used to clamp the membrane during freezing to ensure that no bubbles enter the membrane.

[0021] Preferably, in S3, tweezers are used to clamp the two ends of the frozen membrane in liquid nitrogen and apply force to one side to make the membrane bend and break to form a brittle fracture.

[0022] Preferably, the solution in S4 evaporates completely in more than 30 minutes, and the film changes from translucent to pure white.

[0023] Another aspect of the present invention discloses an electrospinning membrane cross-section sample, wherein the fiber structure and distribution of the electrospinning membrane cross-section sample remain relatively unchanged and is free of impurities.

[0024] The advantages of the present invention compared with the prior art are:

[0025] 1. After the impregnated electrospun membrane is completely frozen, the solidified solution surrounding the fiber is wrapped to prevent the fiber from being disturbed during subsequent brittle fracture. In addition, the tiny crystals near the polymer can act as fillers to enhance the rigidity of the fiber and promote the fiber to transform into brittle failure.

[0026] 2. The clips are made of PET, TPU, and PVC, which have a flat surface. After being added as clips, they can prevent bubbles from being generated in the pores of the electrospinning membrane during freezing, which would destroy the original structure.

[0027] 3. After the membrane is broken and taken out in liquid nitrogen, the solidified low-boiling point solution will evaporate quickly and completely, and will not affect the original composition of the electrospinning membrane.

[0028] Therefore, the samples with smooth and regular cross-sections prepared by this technology can not only accurately observe the original structural characteristics and thickness of different layers of the electrospinning membrane, but can also be used for energy spectrum element analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a SEM image of a cross section of a PVDF electrospinning membrane obtained in a specific embodiment of the present invention

[0030] Figure 2 This is a SEM image of the cross section of a conventional frozen brittle PVDF electrospun membrane of a specific embodiment of the present invention.

[0031] Figure 3 This is a SEM image of the cross section of the PVA / PVDF electrospun composite membrane obtained in a specific embodiment of the present invention.

[0032] Figure 4 is a SEM image of a cross section of a PVDF / PDMS electrospinning composite membrane obtained in a specific embodiment of the present invention

[0033] Figure 5 This is a SEM image of the cross section of the copper mesh / PVDF electrospinning composite membrane obtained in a specific embodiment of the present invention.

[0034] Figure 6 This is a SEM image of the cross section of the PAN / PVDF coaxial electrospinning membrane obtained in a specific embodiment of the present invention.

[0035] Figure 7 It is a SEM image of the cross section of the PAN electrospinning membrane obtained in a specific embodiment of the present invention. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0037] Combined with Figure 1-7As shown, a method for preparing a flat cross-section sample of an electrospun membrane comprises obtaining an electrospun membrane impregnated with a low-boiling point solution, tightly wrapping the electrospun membrane with a clamp, then freezing the membrane to completely solidify the solution in the membrane, breaking the membrane, and obtaining an electrospun membrane cross-section sample after drying.

[0038] The electrospun membrane is completely soaked in a low boiling point solution, wherein the solution includes a uniform solution prepared by any one of methanol, ethanol, isopropanol, dichloromethane, and isopropanol or a combination of two or more, ensuring that the electrospun membrane is completely soaked in the low boiling point solution, the soaking time is greater than 30 minutes, and the air in the membrane is exhausted;

[0039] In order to exhaust the air in the membrane, it can be immersed in a low vacuum environment, and the electrospun membrane can be clamped with a clip, where the upper and lower layers are the clips, and the middle is the electrospun membrane. The clip has a flat surface and is tough under liquid nitrogen freezing, including plastic sheets of PET, TPU, and PVC materials;

[0040] The composite clip is fully frozen with liquid nitrogen. During freezing, tweezers are used to clamp it to ensure that no bubbles enter the composite clip. The composite clip is fully frozen with liquid nitrogen. The freezing time is usually greater than 1 minute to ensure that the solution in the electrospinning membrane is completely solidified. Tweezers are used to clamp the two ends of the frozen composite clip in liquid nitrogen and apply force to one side to bend and break the membrane.

[0041] Embodiment 1:

[0042] Take an electrospinning membrane, which is prepared with PVDF as raw material. After cutting out a thin strip of membrane of suitable size with a length-to-width ratio greater than 5:1, soak it in an ethanol solution for 30 minutes to ensure that the membrane is completely infiltrated. In order to remove the bubbles remaining in the membrane, use a vacuum machine to extract a low vacuum for 1 minute to ensure that the bubbles cannot be observed in the membrane with the naked eye. Then cut out two PVC plastic sheets slightly larger than the membrane, and place them on the upper and lower sides of the infiltrated membrane, respectively, to ensure that the PVC sheet can completely cover the membrane. Clamp the entire composite assembly with tweezers and put it all into the ethanol solution for 30 seconds to ensure that the layers of the composite assembly are completely fitted and no gaps will be generated to cause air to enter. Take enough liquid nitrogen and immerse the composite component completely in liquid nitrogen. Freeze for 30 seconds to ensure that the solution in the composite component is completely solidified. Use two tweezers to clamp the two ends of the membrane respectively, and bend it to the same side at the same time. Take out the composite component after hearing an obvious breaking sound. When the solidified solution melts, take out the electrospun membrane from the two PVC plastic sheets. Wait for 30 minutes to ensure that the ethanol is completely evaporated. The membrane changes from translucent to pure white, and the cross-section sample of the PVDF electrospun membrane is obtained. Observe it with a scanning electron microscope. Figure 1 Another PVDF electrospun membrane cross-section sample was obtained by direct freezing and brittle fracture operation and observed by scanning electron microscope. Figure 2 shown.

[0043] like Figure 1 As shown in the figure, it can be seen that PVDF nanofibers are flexible fibers, but the cross section of the membrane is neatly broken, the fibers are intertwined, and no part of the fibers are obviously separated from the main body of the membrane and extend outward independently. The original structure is well preserved. Figure 2 As shown, there is an obvious stratification phenomenon in the middle of the diaphragm. The reason for this phenomenon is that when the diaphragm enters the liquid nitrogen for freezing, the evaporation of the liquid nitrogen will produce violent bubbles that enter the diaphragm, causing bubbles in the diaphragm to stratify.

[0044] Embodiment 2:

[0045] Take an electrospinning membrane, which is prepared with PVDF and PVA as raw materials. After cutting out a thin strip of membrane of suitable size with a length-to-width ratio greater than 5:1, soak it in an ethanol solution for 30 minutes to ensure that the membrane is completely infiltrated. In order to remove the bubbles remaining in the membrane, use a vacuum machine to draw a low vacuum for 1 minute to ensure that no bubbles can be observed in the membrane. Then cut out two PVC plastic sheets slightly larger than the membrane, and place them on the upper and lower sides of the infiltrated membrane, respectively, to ensure that the PVC sheet can completely cover the membrane. Take enough liquid nitrogen, clamp the entire composite assembly with tweezers, and put it all into the ethanol solution for 30 seconds to ensure that the layers of the composite assembly are completely fitted and no gaps will be generated to cause air to enter. The composite component was completely immersed in liquid nitrogen and frozen for 30 seconds to ensure that the solution in the composite component was completely solidified. Two tweezers were used to clamp the two ends of the membrane respectively, and it was bent to the same side. After an obvious breaking sound was heard, the composite component was taken out. When the solidified solution melted, the electrospun membrane was taken out from the two PVC plastic sheets. Wait for 30 minutes to ensure that the ethanol was completely evaporated. The membrane changed from translucent to pure white, and the cross-section sample of the PVDF / PVA electrospun membrane was obtained. The cross-section sample was observed by scanning electron microscopy. Figure 3 shown.

[0046] like Figure 3 As shown in the figure, the PVDF / PVA composite electrospinning membrane is composed of two nanofibers with different morphologies, of which the thicker ones are PVA nanofibers and the thinner ones are PVDF nanofibers. The elongation and tensile strength of the PVA membrane are weaker than those of PVDF, and the porosity of the membrane layer composed of PVA is slightly larger than that of the PVDF layer. Therefore, when frozen in liquid nitrogen, the PVDF nanofibers still have a ductile fracture, and the PVA nanofibers have a brittle fracture. However, the scanning electron microscope image shows that the cross-sections of the two nanofibers are flat and complete, indicating that the two fibers with different flexibility are broken at the same time to obtain a flat cross-section.

[0047] Embodiment 3:

[0048] Take an electrospinning membrane, which is prepared with PVDF and PDMS as raw materials. After cutting out a thin strip of membrane of suitable size with a length-to-width ratio greater than 5:1, soak it in an isopropanol solution for 30 minutes to ensure that the membrane is completely soaked. In order to remove the bubbles remaining in the membrane, use a vacuum machine to draw a low vacuum for 1 minute to ensure that the bubbles cannot be observed in the membrane with the naked eye. Then cut out two PVC plastic sheets slightly larger than the membrane, and place them on the upper and lower sides of the soaked membrane, respectively, to ensure that the PVC sheet can completely cover the membrane. Take enough liquid nitrogen, clamp the entire composite assembly with tweezers, and put it all into the isopropanol solution for 30 seconds to ensure that the layers of the composite assembly are completely fitted and no gaps will be generated to cause air to enter. The composite component was completely immersed in liquid nitrogen and frozen for 30 seconds to ensure that the solution in the composite component was completely solidified. Two tweezers were used to clamp the two ends of the membrane respectively, and it was bent to the same side. After an obvious breaking sound was heard, the composite component was taken out. When the solidified solution melted again, the electrospun membrane was taken out from the two PVC plastic sheets. Wait for 30 minutes to ensure that the dichloromethane was completely volatilized. The membrane changed from translucent to pure white, and the cross-section sample of the PVDF electrospun membrane was obtained. The cross-section sample was observed with a scanning electron microscope. Figure 4 shown.

[0049] PDMS super-hydrophobic material additives can improve the hydrophobicity of PVDF electrospinning membranes, so the membrane is infiltrated with an isopropanol solution with a smaller surface tension. Figure 4 As shown, microspherical substances are interspersed between PVDF / PDMS fibers, the structure between the membrane layers is compact and there is no separation phenomenon, and the cross-section is neat and flat.

[0050] Embodiment 4:

[0051] Take an electrospinning membrane, which is based on a copper mesh with Cu(OH)2 nanoneedles etched on it, and use electrospinning technology to make a PVDF nanofiber membrane on the copper mesh. Cut out a thin strip of membrane of suitable size according to the specification of aspect ratio greater than 5:1, and soak it in a dichloromethane solution for 30 minutes to ensure that the membrane is completely infiltrated. In order to remove the bubbles remaining in the membrane, use a vacuum machine to extract a low vacuum for 1 minute to ensure that the bubbles cannot be observed in the membrane with the naked eye. Then cut out two PVC plastic sheets slightly larger than the membrane, and place them on the upper and lower sides of the infiltrated membrane respectively to ensure that the PVC sheet can completely cover the membrane. Take enough liquid nitrogen, clamp the entire composite assembly with tweezers, and immerse it in the dichloromethane solution for 30 seconds to ensure that the layers of the composite assembly are completely fitted and there will be no gaps to cause air infiltration. The composite component was completely immersed in liquid nitrogen and frozen for 30 seconds to ensure that the solution in the composite component was completely solidified. Two tweezers were used to clamp the two ends of the membrane respectively, and it was bent to the same side. After an obvious breaking sound was heard, the composite component was taken out. When the solidified solution melted again, the electrospun membrane was taken out from the two PVC plastic sheets. Wait for 30 minutes to ensure that the dichloromethane was completely volatilized. The membrane changed from translucent to pure white, and the cross-section sample of the PVDF electrospun membrane was obtained. The cross-section sample was observed with a scanning electron microscope. Figure 5 shown.

[0052] In order to prevent ethanol from forming a complex with copper hydroxide, the nanofiber membrane was soaked in dichloromethane solution. Figure 5 It can be seen that the Cu(OH)2 nanoneedle structure is intact without any shedding, the copper wire has not been bent or deformed, the PVDF nanofibers are tightly attached to the copper mesh, and the cross-sections of the copper mesh and PVDF are flush.

[0053] Embodiment 5:

[0054] Take an electrospinning membrane, which uses PAN and PVDF as raw materials, and uses wet coaxial electrospinning technology to prepare coaxial nanofibers, in which the fiber core is PAN and the periphery is coated with PVDF. After cutting out a thin strip of membrane of suitable size according to the specification of aspect ratio greater than 5:1, soak it in a 1:1 mixed solution of methanol and ethanol for 30 minutes to ensure that the membrane is completely infiltrated. In order to remove the bubbles remaining in the membrane, the vacuum machine is used to extract low vacuum for 1 minute to ensure that the bubbles cannot be observed in the membrane with the naked eye. Then cut out two PVC plastic sheets slightly larger than the membrane, and place them on the upper and lower sides of the infiltrated membrane respectively to ensure that the PVC sheet can completely cover the membrane. Take enough liquid nitrogen, clamp the entire composite assembly with tweezers, and immerse it in the ethanol solution for 30 seconds to ensure that the layers of the composite assembly are completely fitted and no gaps will be generated to cause air infiltration. The composite component was completely immersed in liquid nitrogen and frozen for 30 seconds to ensure that the solution in the composite component was completely solidified. Two tweezers were used to clamp the two ends of the membrane respectively, and it was bent to the same side. After an obvious breaking sound was heard, the composite component was taken out. When the solidified solution melted, the electrospun membrane was taken out from the two PVC plastic sheets. Wait for 30 minutes to ensure that the solution was completely evaporated. The membrane changed from translucent to pure white, and the cross-section sample of the coaxial electrospun membrane was obtained. It was observed with a scanning electron microscope. Figure 6 shown.

[0055] from Figure 6 It can be seen that due to the compatibility of PAN and PVDF, there is a microporous structure on the periphery of the fiber, the internal PAN part is solid, the inner and outer layers are distinct, and the cross-section is smooth and does not affect the microporous distribution and morphology.

[0056] Embodiment 6:

[0057] Take an electrospinning membrane, which is prepared with PAN as the raw material. After cutting out a thin strip of membrane of suitable size with a length-to-width ratio greater than 5:1, soak it in an ethanol solution for 30 minutes to ensure that the membrane is completely soaked. In order to remove the bubbles remaining in the membrane, use a vacuum machine to extract a low vacuum for 1 minute to ensure that the bubbles cannot be observed in the membrane with the naked eye. Then cut out two PVC plastic sheets slightly larger than the membrane, and place them on the upper and lower sides of the soaked membrane, respectively, to ensure that the PVC sheet can completely cover the membrane. Clamp the entire composite assembly with tweezers and put it all into the ethanol solution for 30 seconds to ensure that the layers of the composite assembly are completely fitted and no gaps will be generated to cause air to enter. Take enough liquid nitrogen and completely immerse the composite component in liquid nitrogen. Freeze for 30 seconds to ensure that the solution in the composite component is completely solidified. Use two tweezers to clamp the two ends of the membrane respectively, and bend it to the same side at the same time. Take out the composite component after hearing an obvious breaking sound. When the solidified solution melts, take out the electrospun membrane from the two PVC plastic sheets. Wait for 30 minutes to ensure that the ethanol is completely evaporated. The membrane changes from translucent to pure white, and the PA electrospun membrane cross-section sample is obtained. Observe it with a scanning electron microscope. Figure 7 As shown: Due to the extremely strong plasticity of PAN nanofibers, the cross-section is extremely complete after being frozen and solidified in ethanol.

[0058] Based on the above implementation cases, compared with the cross-section obtained by directly using liquid nitrogen freezing and brittle fracture, the cross-section of the electrospun fiber membrane obtained by this method is more neat and has no plastic deformation, which is very conducive to observing the original cross-sectional state of the electrospun fiber membrane.

[0059] The method provided by the present invention to obtain the brittle fracture section of the flexible membrane overcomes the two problems mentioned above. First, since there is no direct connection between the electrospinning electrospinning fiber membrane filaments, when frozen by liquid nitrogen, the fiber filaments are easily disturbed by air and cause separation between the membrane layers (this problem is particularly prominent in composite membranes).

[0060] The present invention uses PVC plastic clips, which facilitates the preparation of small samples and gives an inward pressure to the membrane between the clips, inhibiting the bulging of the membrane layer during liquid nitrogen freezing. Second: Although the electrospun fiber membrane is more brittle at low temperatures than at room temperature, many samples still have a certain toughness at liquid nitrogen temperature. The electrospun fiber membrane brittle fracture method provided by the present invention uses a high freezing point solution to fully infiltrate the membrane, and then uses liquid nitrogen to cool the solution around the electrospun fiber to solidify, limiting the movement of the electrospun fiber, while providing a larger concentrated stress and a high strain rate, so that the electrospun fiber is subjected to concentrated and large tensile stress and breaks quickly, achieving a better brittle fracture effect.

[0061] In addition, the raw materials used in the preparation method of the present application are cheap, easily available, and the preparation process is simple, and can be widely promoted and used.

[0062] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.

Claims

1. A method for preparing a flat and lossless cross-section sample of an electrospinning membrane, characterized in that: The following steps are involved: S1: Use low boiling point solution to completely wet the electrospun membrane and remove residual bubbles; S2: Use a clamp to completely cover and clamp the electrospun membrane to form a membrane sheet, and place the membrane sheet in liquid nitrogen to fully cool it; S3: brittle fracture of electrospun membrane after cooling; S4: Take out the middle electrospun membrane and wait for the solution to evaporate completely to obtain a smooth and intact electrospun brittle membrane sample.

2. The method for preparing a flat and lossless cross-section sample of an electrospinning membrane according to claim 1, characterized in that: The low boiling point solution includes a uniform solution prepared by any one of methanol, ethanol, isopropanol and dichloromethane or a combination of two or more thereof.

3. The method for preparing a flat and lossless cross-section sample of an electrospinning membrane according to claim 2, characterized in that: The soaking time in S1 is greater than 30 minutes, and the removal of residual bubbles includes sending the soaked electrospun membrane into a vacuum machine for vacuuming for 1 minute.

4. The method for preparing a flat and lossless cross-section sample of an electrospinning membrane according to claim 2, characterized in that: The step S1 includes soaking the electrospinning membrane in a low boiling point solution under a low vacuum environment.

5. The method for preparing a flat and lossless cross-section sample of an electrospinning membrane according to claim 1, characterized in that: The clip has a flat surface and is tough under liquid nitrogen freezing, and comprises a sheet made of PET, TPU, or PVC materials.

6. The method for preparing a flat and lossless cross-section sample of an electrospinning membrane according to claim 1, characterized in that: The step S2 further includes soaking the clamped membrane twice in a low boiling point solution and then cooling it with liquid nitrogen, wherein the soaking time is greater than 30 seconds.

7. The method for preparing a flat and lossless cross-section sample of an electrospinning membrane according to claim 1, characterized in that: In S2, liquid nitrogen is used to fully freeze the composite clip. The freezing time is greater than 1 minute until the solution in the electrospinning membrane is completely solidified. Tweezers are used to clamp it during freezing to ensure that no bubbles enter the membrane.

8. The method for preparing a flat and lossless cross-section sample of an electrospinning membrane according to claim 1, characterized in that: The electrospinning membrane in S1 is made of one or more combinations of PVDF, PVA, PDMS, copper mesh, and PAN.

9. The method for preparing a flat and lossless cross-section sample of an electrospinning membrane according to claim 1, characterized in that: The solution in S4 evaporates completely after more than 30 minutes, and the film changes from translucent to pure white.

10. An electrospun membrane cross-section sample, obtained according to the method for preparing a flat and lossless electrospun membrane cross-section sample according to any one of claims 1 to 9, characterized in that: The fiber structure and distribution of the electrospinning membrane cross-section sample remain relatively unchanged and free of impurities.

Citation Information

Patent Citations

  • Preparation method of thin-film material section scanning electron microscope sample

    CN111721792A

  • Preparation method of filter membrane section sample

    CN113686632A

  • Method for preparing section SEM sample by micropore thin film material

    CN103512785A

  • Flexible film brittle failure method

    CN105699167A

  • Transfer method of wafer-level-scale graphdiyne film

    CN113471145A